Trends in the Utilization of Outsourced Marketing Departments by Landlords of Boarding Rooms in Ho Chi Minh City (International Journal of Scientific Research and Management (IJSRM), 2024)
In an era marked by escalating competition, the adoption of Outsourced Marketing practices emerges not only as a cost-saving measure but also as a catalyst for the enhancement of operational efficiency, and market competitiveness. The deployment of outsourced marketing strategies proves to be especially germane to the operational business of boarding-room enterprises in Ho Chi Minh City, rooted in features of operational scale, industry domain specificity, and responsiveness to evolving technological paradigms and consumer information acquisition demand. Fundamental advantages of outsourced marketing services to boarding room landlords encompass cost mitigation; revenue augmentation; simultaneously, increased time for specialized pursuits, brand equity amplification, and recognition level for the rental rooms system. This article principally discusses the trends in the utilization of outsourced marketing departments by boarding room landlords in Ho Chi Minh City, according to three focal domains: (1) The scale of outsourcing, (2) Process of managing and performing outsourced marketing, (3) The influence of outsourced marketing on the operational outcomes of boarding rooms enterprises.